Design and Construction of Automatic Salted Fish Drying Device Based on Microcontroller - Yuliza, Milda; Yultrisna; Efrizon; Chandranata, Adi; Kurnia, Ella (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
An Automatic Salted Fish Dryer controlled by a microcontroller has been made based on a drying process that takes a long time, which is around 3-4 days and the weather is also sometimes unpredictable, thus inhibiting the productivity of making salted fish. The purpose of this study is to design a salted fish dryer that can work automatically to speed up the drying process of salted fish by maintaining a temperature that does not exceed 45 ° C to obtain a salted fish humidity of 40%. The research method starts from making a prototype and measuring system performance. The results of measuring the performance of drying salted fish using an automatic salted fish dryer are faster than the traditional method which requires a drying time of 3-4 days. By using an automatic dryer, it only takes 3-5 hours of drying and can reduce fish humidity by up to 40%, in accordance with SNI with a maximum drying temperature of 45 ° C. The DHT22 sensor is used to measure temperature and humidity, which is then displayed on the LCD. Overall, the tool can function well. Suggestions for further research, Hybrid energy sources can be added and condition monitoring can be done via the Internet of things (IoT).